High-throughput metabolomics exploring the pharmacological effects and mechanism of icariin on rheumatoid arthritis rat based on ultrahigh-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry - Peng Zhou; Xixi Liu; Yushi Tian; Shouze Ren; Hua Liang (Frontiers in Molecular Biosciences)
IntroductionMetabolomics could provide insights into the pharmacological effects and action mechanisms of drugs through assessment of the changes in relevant biomarkers and biological pathways. Icariin (ICA) is a promising ffavonoid compound known to have significant anticancer activity; however, the pharmacological mechanisms of ICA in the treatment of rheumatoid arthritis (RA) need to be explored further.MethodsThe changes in the metabolic profiles of serum samples were revealed using non-targeted metabolomics based on ultrahigh-performance liquid chromatography coupled with quadrupole time-of-fight mass spectrometry. Tissue histopathology, physical parameters, and biochemical indicators were also measured and analyzed to reveal the mechanisms of ICA in the treatment of RA.Results and discussionThirty-one potential biomarkers were identified to highlight the metabolic disorders in an RA animal model, out of which twenty-three were regulated by ICA treatment. These biomarkers were mainly involved in alanine, aspartate, and glutamate metabolism; arachidonic acid metabolism; citrate cycle; pyruvate metabolism; and glycolysis/gluconeogenesis pathways. The anticancer mechanism of ICA on RA may be attributed to amelioration of the amino acid metabolism, unsaturated fatty acid metabolism, citrate cycle, pyruvate metabolism, and others, which in turn regulate the oxidative stress state and inflammatory effects. Thus, metabolomics is a promising approach for revealing the biomarker distribution and pathways of RA to determine the effects and mechanisms of ICA, which can benefit the development of natural medicines.